FRI0472 Towards a multidimensional patient reported outcome measures assessment: development and validation of a questionnaire for patients with systemic sclerosis/scleroderma. (12th June 2018) - El Miedany, Y.; El Gaafary, M.; El Aroussy, N.; Youssef, S.; Atef, Y.; Palmer, D.
Abstract : Background: Systemic sclerosis is a chronic multisystem autoimmune disorder associated with high morbidity and mortality rates. A multidisciplinary approach is necessary due to the complexity of the disease and its associated multi-organ affection. It is important to understand and monitor the impact of systemic sclerosis on the patients, provide them with high quality of care and to endorse the ownership of their disease process as early as possible to prepare them for the management this life-long illness. Objectives: To assess the validity, reliability of a specific multidimensional patient self-reported questionnaire that can assess construct outcome measures of patients with systemic sclerosis/scleroderma. Methods: The questionnaire was developed by integrating information obtained from patients suffering from systemic sclerosis as well as scleroderma based on the Rasch model. The questionnaire includes assessment of functional disability, quality of life, 0–10 numeric visual analogue scale (VAS) to rate the severity of the musculoskeletal pain, difficulty in breathing, gastrointestinal symptoms (e.g. swallowing difficulty/reflux/bloating/Faecal soilage/diarrhoea/constipation), Raynaud's phenomenon, fingers ulcers as well as the global assessment of the disease impact on the patient's life. In addition, the questionnaire includes 2 mannequins, one for self-reported body pains and the other one for self-reported skin tightness. Also there is a review of the possible comorbidities for the patient to tick infront of whatever he/she developed in the past month; as well as patient motivation. The questionnaire was completed by 52 consecutive patients with systemic sclerosis 31 and scleroderma. 21 Results: The multidimensional PROMs questionnaire was reliable as demonstrated by a high-standardised alpha (0.894–0.993). The questionnaire items correlated significantly (p<0.01) with clinical parameters of disease activity. Patient reported tender spots and skin tightness correlated significantly with the physician's as well as Rodnan skin scores (correlation coefficient 0.848 and 0.821 respectively). Changes in functional disability, quality of life and motivation scores showed significant variation (p<0.01) with diseases activity status. The PROMs questionnaire showed also a high degree of comprehensibility (9.3). Conclusions: The developed PROMs questionnaire is a reliable and valid instrument for assessment of patients suffering from systemic sclerosis/scleroderma. Being short, rapid and comprehensive, this adds more to its applicability. The data support the value of completion of the simple 2 pages patient questionnaire, which provides a quantitative written documented record by the patient, at each visit to the rheumatologist. Disclosure of Interest: None declared